Analisis Ring of Security pada Stasiun MRT X - Permana, Aulya; Priyanto, Sapto (Universitas Ekasakti, 2024)
The security of public transportation infrastructure is a crucial aspect in maintaining the stability and continuity of urban society. Mass Rapid Transit (MRT) stations are potential targets for terrorism and other crimes. This study aims to analyze the security of X MRT Station based on the Ring of Security concept. This article, titled